Liquidity efficiency and distribution in the LVTS: Non-neutrality of system changes under network asymmetry - Sean O'Connor; James Chapman; Kirby Millar (Bank of Canada, 2008)
The authors consider the liquidity efficiency of Tranche 2 of the Large Value Transfer System (LVTS T2) by examining, through an empirical analysis, some plausible strategic reactions of individual participants to a systemwide shock to available liquidity in the system. The network structure of the LVTS T2 is found to be asymmetric in terms of the patterns of out-payment flows. It is composed of three subgroups, in which participants within a subgroup are more strongly linked with each other than with participants in other subgroups. Three possible network equilibria are proposed. The equilibria are defined in terms of participant-specific collateral needs and out-payment delays, and result from different relative cost structures involving collateral costs, queuing costs, and payment delay penalties. Each of the conjectural equilibria relate to a dominant strategy for at least those participants most central in the network with respect to liquidity transfer adopted network-wide as a common strategy.
Keywords: L14; L13; G21; 330; Payment; clearing; and settlement systems; Financial services; Financial institutions; Bankensystem; Zahlungsverkehr; Verrechnungsverkehr; Bankenliquidität; Finanzdienstleistung; Netzwerk; Kosten